Rice husk and saw dust as filter loss control agents for water-based muds - Okorie E. Agwu; Julius U. Akpabio; Glory W. Archibong (Heliyon, 2019)
When drilling with water based muds (WBM), significant fluid loss volumes from the mud into the formation can have adverse effects not just on the mud and its properties but also on the stability of the wellbore. Prevention of mud filter loss is one way of assessing the performance of a drilling mud. However, evaluation of the effectiveness or otherwise of a fluid loss control additive can be made by characterizing the mud cake formed. Interestingly, the mud cake characterization is one area that has been somewhat neglected in drilling fluid formulation with agro waste materials. Two cellulosic materials - rice husk and saw dust were chosen for the experimental study. The specie of the rice husk used was the African rice (Oryza glaberrima) while the dust from the saw milling of Oxystigma manni was utilized for this study. To ensure result acceptability, the rice husk and saw dust were ground and the resulting products were sieved to 1.25 × 10−4 m. The filtration characteristics of the formulated mud samples were tested using the American Petroleum Institute (API) filter press and in accordance to the API recommended practice for field testing WBMs. From the filter loss tests, it was observed that the ground rice husk prevented filter loss by an average of 77% compared to ground saw dust filtration control of 63%. In addition, it was observed that at higher concentrations, ground saw dust and rice husk prevented fluid loss to the minimum acceptable API standard. For the filter cake thickness measured in millimetres, ground rice husk exhibited thicker mud cakes when compared with the saw dust by an average amount of 14%. For the mud cake characteristics, the rice husk mud exhibited smooth and slippery cakes while the saw dust mud exhibited rough texture, sticky and firm cakes.